Review of prostate cancer genomic studies in Africa - Samtal, Chaimae; El Jaddaoui, Islam; Hamdi, Salsabil; Bouguenouch, Laila; Ouldim, Karim; Nejjari, Chakib; Ghazal, Hassan; Bekkari, Hicham (Frontiers in Genetics, 2022)
Prostate cancer (PCa) is the second leading cause of mortality worldwide and one of the most frequent cancers in men in Africa. The heterogeneity of this cancer fosters the need to identify potential genetic risk factors/biomarkers. Omics variations may significantly contribute to early diagnosis and personalized treatment. However, there are few genomic studies of this disease in African populations. This review sheds light on the status of genomics research on PCa in Africa and outlines the common variants identified thus far. The allele frequencies of the most significant SNPs in Afro-native, Afro-descendants, and European populations were compared. We advocate how these few but promising data will aid in understanding, better diagnosing, and precisely treating this cancer and the need for further collaborative research on the genomics of PCa in the African continent.